SIEGE - IV. Compact star clusters in cosmological simulations with a high star formation efficiency and subparsec resolution - Pascale, Raffaele; Calura, F.; Vesperini, E.; Rosdahl, J.; Nipoti, C.; Giunchi, E.; Lacchin, Elena; Lupi, A.; Messa, M.; Meneghetti, M.; Ragagnin, A.; Vanzella, E.; et al. (Astronomy and astrophysics, 2025)
The formation of compact high-redshift star-forming clumps, along with the physical processes driving their evolution and their potential connection to present-day globular clusters (GCs), are key open questions in studies of galaxy formation. In this work, we aim to shed light on these aspects using the SImulating the Environment where Globular clusters Emerged (SIEGE) project, a suite of cosmological zoom-in simulations with subparsec resolution that is specifically designed to investigate the physical conditions behind the origin of compact stellar systems in high-redshift environments. The simulations analyzed in this study are focused on a dwarf galaxy with a virial mass of a few 10 9 M⊙ at z = 6.14, where the spatial resolution reaches 0.3 pc h −1. Individual stars are formed directly by sampling the initial mass function, with a 100% star formation efficiency. This setup is designed to explore the impact of a high star formation efficiency under high-redshift conditions. The simulation reveals the emergence of numerous stellar clumps with sizes of 1-3 pc, stellar surface densities up to almost 10 4 M⊙ pc −2, and masses predominantly spanning 10 3 M⊙ to several 10 4 M⊙, with a few reaching 10 5 M⊙ and up to 10 6 M⊙. All clumps form during intense, short bursts of star formation lasting less than a megayear, without noticeable signs of second peaks of star formation or accretion, often with negligible dark matter content (i.e., dark-to-stellar mass ratios below 1 within three times their effective radii). We measured a clear correlation between mass and size, with a clump mass function described by a power law with a slope of −2. Star formation conditions in the simulation reveal a behaviour that is similar to that of a feedback-free starburst scenario, where dense clumps form due to inefficient stellar feedback over small timescales. Notably, some clumps exhibit properties that closely resemble those of present-day globular clusters, highlighting their potential evolutionary connection.
Online veröffentlicht: 27. Juni 2025
Gesehen am 06.11.2025